Knowledge, attitudes and practices of HIV-positive patients regarding disclosure of HIV results at Betesda Clinic in Namibia - Penelope Tom (AOSIS, 2013)
Background: This study examined the practices, knowledge, attitudes, and the reasons for disclosure and non-disclosure of HIV-positive patients with regard to the disclosure of HIV results at Betesda Clinic in Windhoek, Namibia.Objectives: The objectives of the study were to determine knowledge, attitudes, and practices of HIV-positive patients regarding the disclosure of HIV status at Betesda Clinic in Namibia, and to determine the reasons for disclosure and non-disclosure.Methods: This was a cross-sectional descriptive study and 263 HIV-positive patients were enrolled in the study.Results: Analyses revealed that knowledge on disclosure was good, with 68% who thought it was important. The majority (73%) have disclosed and 60% disclosed within 1 week of receiving their results. The most common reasons for disclosure were that 32% needed help, 25% wanted his or her partner to go for testing, and 20% wanted to let relatives know. Reasons for non-disclosure were mainly the fear of gossip (79%). Seventy-three per cent had disclosed to their partners, and 23% had disclosed to more than one person. People's reactions were supportive in 43%, whereas 29% understood, 9% accepted and 6% were angry. Upon disclosure 40% received help, 24% of partners were tested, 23% received psychological support and 5% were stigmatised. Disclosure was higher amongst the married and cohabitating.Conclusion: The attitude was positive with regard to knowledge of disclosure, with most participants thinking that disclosure was important and good. The attitudes and actual practices of disclosure were encouraging; however, people are disclosing only to trustedindividuals in the society and the fear of stigma is still present although the actual stigma was very low.